2019
DOI: 10.1002/jcb.28947
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myeloid differentiation 1 specifically in colon with antisense oligonucleotide exacerbates dextran sodium sulfate‐induced colitis

Abstract: Myeloid differentiation 1 (MD‐1), also known as lymphocyte antigen 86 (Ly86), is a soluble protein homologous to MD‐2 and forms a complex with radioprotective 105 (RP105). RP105/MD‐1 complex negatively regulates toll‐like receptor 4 (TLR4) signaling and is involved in several immune disorders. However, the precise role of MD‐1 in inflammatory bowel diseases (IBD) remains poorly understood. To further investigate the involvement of MD‐1 in IBD, we inhibited MD‐1 in colon with antisense oligonucleotide (AS‐ODN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It is commonly reported that MD-1, also called Ly86, is involved in multiple pathological processes and cellular events, especially the activation of inflammation through the formation of complexes with RP105 [33]. For instance, Chen et al showed that MD-1 loss exacerbates dextran sodium sulfate-elicited colitis [34]. The important roles of RP105/MD-1 in the regulation of HF-caused insulin resistance and inflammation were also demonstrated in a previous study [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly reported that MD-1, also called Ly86, is involved in multiple pathological processes and cellular events, especially the activation of inflammation through the formation of complexes with RP105 [33]. For instance, Chen et al showed that MD-1 loss exacerbates dextran sodium sulfate-elicited colitis [34]. The important roles of RP105/MD-1 in the regulation of HF-caused insulin resistance and inflammation were also demonstrated in a previous study [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that LY86 forms a complex with Toll-like receptor protein RP105 and is involved in several immune disorders [24][25][26]. Depending on the cell type, this complex has opposite regulatory effects on TLR4 signaling [27,28]; while TLR4 signaling is activated and stimulates proliferation and antibody production in B-cells, it is negatively regulated in myeloid cells.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Lymphocyte antigen 86 (LY86), also known as MD-1, can form a complex with radioprotective 105 (PR105) to block the TLR4/MD-2 complex and, thus, attenuate in ammation via the NF-KB signaling pathway [31]. Therefore, an RP105 de ciency can lead to a slower progression of early atherosclerotic plaques [32].…”
Section: Discussionmentioning
confidence: 99%